Computation of Electromagnetic Fields for 220 kV Power Line in Cartagena de Indias (2019)
The growth of the cities towards the suburban areas has caused that the buildings are construct near the lines of high voltage. This has led to detailed studies of the electric and magnetic fields generated by these lines to determine the potential impact on the health of people within their area of influence. Therefore, it is necessary to calculate the profiles of the electric and magnetic fields, near the high voltage lines as a function of the distance to the center of the same and determine if the values are within the exposure limits accepted by national and international organizations. To achieve this, a program was written in Matlab that performs the calculation of the electric and magnetic field profiles under the power transmission lines based on fundamental laws. The results were validated by measurements made in accordance with the procedures established by IEEE in a 220 kV electric transmission line located in the city of Cartagena de Indias. © 2019, Springer Nature Switzerland AG.